2016
DOI: 10.1039/c5an01970b
|View full text |Cite
|
Sign up to set email alerts
|

The anti-atherosclerotic effect of tanshinol borneol ester using fecal metabolomics based on liquid chromatography-mass spectrometry

Abstract: Tanshinol borneol ester (DBZ) is a novel experimental compound that consists of two chemical structural units from danshensu and borneol. It exhibits efficacious anti-ischemic and anti-atherosclerosis activities in rats. A fecal metabolomics based on Liquid Chromatography-Mass Spectrometry combined with clinical histopathology and blood lipid estimation was employed to assess the efficacy and the metabolic changes caused by administration of DBZ in atherosclerotic rats. There were the typical pathological feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Regarding phosphatidylglycerol (PGs), which a phosphoglycerol moiety occupies a glycerol substitution site, little evidence has been shown on their relationship with CHD, and we were the first to reveal a positive relationship between PG ( 20:3/2:0) and CHD (OR: 3.938; 95% CI: (1.891, 8.204); P = 0.0001) in human plasma. Several previous studies have provided evidence that PGs are significantly increased in atherosclerotic rats 45 , 46 . Elevated levels of PGs were also found in patients with type 2 diabetes and prediabetes 47 .…”
Section: Discussionmentioning
confidence: 96%
“…Regarding phosphatidylglycerol (PGs), which a phosphoglycerol moiety occupies a glycerol substitution site, little evidence has been shown on their relationship with CHD, and we were the first to reveal a positive relationship between PG ( 20:3/2:0) and CHD (OR: 3.938; 95% CI: (1.891, 8.204); P = 0.0001) in human plasma. Several previous studies have provided evidence that PGs are significantly increased in atherosclerotic rats 45 , 46 . Elevated levels of PGs were also found in patients with type 2 diabetes and prediabetes 47 .…”
Section: Discussionmentioning
confidence: 96%
“…DBZ was dissolved in 2% Kolliphor ® P 188 to give a final concentration of 4.0 mg/mL. The solutions were administered to the rats via intravenous injection with a dosage of 20 mg/kg (Jia et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been proved that DBZ can promote angiogenesis through activating Akt and MAPK signalling pathways (Liao, Fan, Zhao, Choi, & Zheng, ). In addition, DBZ exhibits distinct anti‐atherosclerosis effects (Jia et al, ), suppresses lipopolysaccharide‐induced macrophage activation and lipid accumulation in vitro (Xie et al, ), and reduces atherosclerotic lesion formation by inhibiting inflammation and decreasing macrophage infiltration into the vessel wall of apolipoprote E‐deficient mice (Wang et al, ). The investigations above suggest that DBZ will become a promising new drug for treating cardio‐cerebrovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous studies have shown that DBZ is beneficial in patients with cardiovascular and cerebrovascular disease and that its therapeutic effects are better than either DSS or borneol alone. [2][3][4][5] Additionally, DBZ can be conveniently prepared for various dosage forms compared with a mixture of water-soluble DSS and water-insoluble borneol.…”
Section: Introductionmentioning
confidence: 99%